Genetic Aspects of Plant Mineral Nutrition 1987
DOI: 10.1007/978-94-009-3581-5_23
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of inbred maize lines for aluminum tolerance in nutrient solution

Abstract: Key words AI and P levels to assess AI toleranee Brazilian and USA inbred lines Plant measurements for AI toleranee Zea mays Summary Maize (Zea mays L.) inbred lines were grown in nutrient solution with different levels of AI and P to study their genetie variability for AI toleranee. Plant measurements for determining inbred line responses to AI wc re also evaluated. The best traits to assess maize for AI toleranee were seminal and adventitious root lengths.Brazilian maize inbred lines were mare tolerant to AI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
4

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 12 publications
2
50
0
4
Order By: Relevance
“…Por outro lado, para o CLRS observaram-se coeficientes de correlação positivos e baixos (r = 0,33** e r = 0,10 aos três e sete dias de germinação, respectivamente), indicando que este índice, aos três dias de germinação, tende a favorecer plântulas com maior CIRS . Estas estimativas confirmam a tendência de coeficientes de correlação positivos em relação ao CLRS e negativos em relação ao CRRS obtidos por Magnavaca et al (1987a), que ao realizar este mesmo tipo de abordagem relatou valores de r = -0,02 para CRRS e r = 0,31** para CLRS.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Por outro lado, para o CLRS observaram-se coeficientes de correlação positivos e baixos (r = 0,33** e r = 0,10 aos três e sete dias de germinação, respectivamente), indicando que este índice, aos três dias de germinação, tende a favorecer plântulas com maior CIRS . Estas estimativas confirmam a tendência de coeficientes de correlação positivos em relação ao CLRS e negativos em relação ao CRRS obtidos por Magnavaca et al (1987a), que ao realizar este mesmo tipo de abordagem relatou valores de r = -0,02 para CRRS e r = 0,31** para CLRS.…”
Section: Resultsunclassified
“…Testando quatro diferentes tipos de índices fenotípicos para avaliação da tolerância ao Al, Magnavaca et al (1987a) concluíram que o comprimento relativo da raiz seminal (CRRS) foi o mais adequado para este tipo de avaliação, por ser o único a possibilitar correções quanto às diferenças de vigor que ocorrem durante a germinação. Por outro lado, Prioli (1987) verificou que o comprimento líquido da raiz seminal (CLRS) foi mais eficiente quando comparado com o CRRS, por apresentar menores coeficientes de variação.…”
Section: Introductionunclassified
“…RRG and hematoxylin staining have proved to be suitable phenotypic criteria for assessing Al tolerance in maize in full nutrient solution (Magnavaca et al, 1987;Cançado et al, 1999). The South American maize single cross (SLP 181/ 71 ϫ Cateto Colombia 96/71) used in the present study showed a high level of Al tolerance, as indicated by the small (about 30%) root growth inhibition observed in solutions containing up to 450 m Al (80 m Al 3ϩ activity).…”
Section: Al Tolerance and The Spatial Distribution Of The Al-activatementioning
confidence: 99%
“…This leads to the speculation that Al-activated transport and synthesis may be coupled in Al-tolerant maize. Furthermore, it appears that Al tolerance in maize is a genetically complex trait (Magnavaca et al, 1987) that could involve several different Al tolerance mechanisms. These data lead us to speculate that there could be an Al exclusion tolerance mechanism based on citrate exudation, and a second internal tolerance mechanism using increases in internal levels of Alchelating citrate.…”
Section: Differences In Al-activated Organic Acid Transport and Root mentioning
confidence: 99%
“…After germination for 4 days, the endosperm was removed from the seeds to eliminate the nutritional reserves, especially P (Rose et al, 2013), and three uniform seedlings were selected for each of the three replicates. The experimental design was completely randomized, with three replicates, and two treatments: LP and HP at 2.5 and 250 µM P, respectively, in a modified Magnavaca nutrient solution (Magnavaca et al, 1987). A system consisting of plastic file folders lined with germination paper was used for hydroponic growth (de Sousa et al, 2012).…”
Section: Methodsmentioning
confidence: 99%